Surface and Catalytic Properties of MoO-Treated CoO/AlO Solids - A.M. Ghozza; G.A. El-Shobaky; G.M. Mohamed (Adsorption Science & Technology)
The surface and catalytic properties of Co 3 O 4 /Al 2 O 3 solids treated with different proportions of MoO 3 were investigated, the extent of MoO 3 added varying between 0.50 mol% and 5.00 mol% (0.63–5.9 wt%). The pure sample was prepared by thermal decomposition at 600°C of aluminium hydroxide impregnated with a calculated amount of Co(NO 3 ) 2 dissolved in the least amount of distilled water. The MoO 3 -treated samples were prepared by thermal decomposition at 600°C of aluminium hydroxide treated with different proportions of ammonium molybdate followed by treatment with Co(NO 3 ) 2 solution. The crystalline phases produced by thermal treatment of the pure and treated samples precalcined at 600°C were characterized using an XRD technique. The surface and catalytic properties of the various catalysts were studied using nitrogen adsorption at −196°C and CO oxidation by O 2 at 100–150°C. The results obtained revealed that molybdena treatment of the Co 3 O 4 /Al 2 O 3 solids followed by precalcination at 600°C resulted in a decrease in the degree of crystallinity of the Co 3 O 4 phase produced. This treatment effected a progressive small increase in the specific surface area of the treated solids (ca. 10%). However, the catalytic activity was found to be increased considerably by increasing the amount of MoO 3 added (184%), reaching a maximum limit at 1.00 mol% MoO 3 . The activation energies of the catalytic reaction calculated for both the pure and MoO 3 -treated solids suggested that MoO 3 treatment did not modify the energetic nature of the active sites (surface cobalt species) but increased their concentration.